Minimum breast distance largely explains individual variability in doses to contralateral breast from breast-cancer radiotherapy. (February 2019) - Kundrát, Pavel; Remmele, Julia; Rennau, Hannes; Sebb, Sabine; Simonetto, Cristoforo; Eidemüller, Markus; Wolf, Ulrich; Hildebrandt, Guido
Highlights: Doses to contralateral breast differ largely among breast-cancer patients. This variability is related to patient anatomy. Minimum breast distance explains 60% of this variability for tangential techniques. Personalized dose and risk estimates are enabled. Abstract: Purpose: To provide personalized estimates of doses to contralateral breast (CB) from breast-cancer radiotherapy. Methods: Whole-breast irradiations using 3D conformal, intensity-modulated and hybrid techniques with 50.4 Gy prescribed dose were planned for 128 breast-cancer patients. From their CT images, 17 anatomic measures were assessed and tested by model fitting as predictors for CB dose–volume characteristics. Results: Multi-field intensity-modulated radiotherapy (IMRT) yielded mean CB doses of 0.8–7.1 Gy, with no correlation to the studied anatomic parameters. Tangential whole-breast irradiation led to much lower mean CB doses, 0.2–1.6 Gy. About 60% of this inter-patient variability was explained by individual variations in a single anatomic measure, the minimum breast distance (MBD), defined as the CB distance from the tangent to the treated breast. Per 1 cm increase in MBD, the mean CB dose decreased by 10–15%. As an alternative to MBD, dose estimates could be based on the breast-to-breast distance, which is highly correlated with MBD. Conclusion: The results enable personalized assessment of CB doses from tangential whole-breast irradiation, based only on parameters assessable from CT data. This may help support clinical decision-making processes as well as analyse retrospective studies on CB risks.